Factors associated with occasional and recurrent falls in Mexican community-dwelling older people - Agudelo-Botero, Marcela (PLoS One, 2018)
Falls are a frequent event among older adults that can cause wounds, disability, psychological disorders, and premature death. Although the large number of existing studies on the issue, few have been conducted in middle- and low-income countries. The objective of the present study is to identify the sociodemographic, medical, and functional performance factors associated with occasional and recurrent falls in Mexican older adults dwelling in community. Cross-sectional analysis of 9 598 adults ≥60 years old who participated in the fourth round (2015) of the Mexican Health and Aging Study. Bivariate tests were performed to evaluate the differences between covariates by distinct fall groups (no falls, occasional falls, and recurrent falls). Multiple logistic regressions with unadjusted and adjusted models were estimated. Approximately 46% of older adults had had at least one fall during the previous two years (one fall 16% and recurrent falls 30%). Occasional falls were only associated with being a woman; in addition to the sex, recurrent falls were strongly associated with advanced age, rural residence, bad and very bad self-perception of health status, activity-limiting pain, urinary incontinence, depression, arthritis, limitations in basic activities of daily living, and limitations in advanced activities of daily living. Falls, primarily recurrent falls, deserve to be addressed through multifactorial strategies that include different areas of intervention.